Kryzys zadłużeniowy a sytuacja materialna gospodarstw domowych w Polsce - Januszewska, Małgorzata J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
To sum up, the data used in this article and the described economic mechanisms show that there is strong correlation between the public debt level and the situation of households. Nowadays, it can bring many negative consequences. The private and public debts in Poland are reaching about 16 030 mld zł. Government safes the budget with bufet defi cyt, and the private savings of consumer are gone with growing consumption outways. Governemtn is affraid about zloty’s rate of exchange and thousands of debtors wonder how high will the next instalment be. Growing uneployment taxes caused impoverishment, though nominally nothing has changed. The latter case had one positive effect decrease of budget defi cyt of the current year but it is still not enough. If the debt will not drop, the state will not manage to help its citizens and it will take a lot of common work to rebuild the economic growth.
Keywords: gospodarstwa domowe; kryzys zadłużeniowy; sytuacja finansowa; Polska